Outpatient clinics for adults with congenital heart disease: increasing workload and evolving patterns of referral. Issue 1 (1st January 1999) - Gatzoulis, M A; Hechter, S; Siu, S C; Webb, G D
Abstract : Objective: To examine the evolving role of specialised outpatient services for adult patients with congenital heart disease. Design: A retrospective analysis of all patients attending the Toronto Congenital Cardiac Centre for Adults over three corresponding three month periods in 1987, 1992, and 1997. Setting: A tertiary referral centre. Main outcome measures: Patient demographics, residence, medical and surgical history, type and source of referral, and investigations performed. Results: In all, 570 patients were seen at the clinic during these three periods. There was a 44% and a 269% increase in workload between 1987 to 1992 and 1992 to 1997, respectively. There was a steady fall in mean age of patients seen at the clinic with time (38.5, 33.6, and 31.7 years in 1987, 1992, and 1997, respectively, p < 0.001). New referrals from community cardiologists and family physicians increased more in relative terms than did referrals from the Hospital for Sick Children, Toronto (6.7%, 15%, and 37.5%, p = 0.02). There was a steady increase in patients with previous reparative surgery (48.9%, 59.2%, and 69.2%, p < 0.002). The proportion of patients with previous reoperations also increased (2.3%, 10%, and 9.2%, p < 0.01). Echocardiography remained the predominant method of diagnosis. The diagnostic mix did not change with time. Conclusions: Over the past 10 years there has been a large increase in adults with congenital heart disease requiring and seeking specialised care in a tertiary health centre, with a concomitant evolution of referral patterns. These data may be helpful in planning of similar paediatric and adult cardiac services for this expanding population.